2008
DOI: 10.1353/cpr.2008.0010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Community Resource Assessments in the Development of 15 Adolescent Health Community-Researcher Partnerships

Abstract: Background-Connect to Protect (C2P): Partnerships for Youth Prevention Interventions is an initiative that alters the community's structural elements to reduce youth HIV rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Other studies identifying barriers to accessing health and social services have reported high rates of self-reported access issues, and have identi ed that those reporting access issues were more likely to be socially and economically vulnerable or suffering from mental health conditions indicating that those who have the hardest time accessing services may be the most in need 16,17 . Studies identifying how barriers to clinical and social services can be reduced use targeted social support interventions and speci c navigation models to promote patient-centered health improvements 18 as well as strategies to evaluate local resources to develop partnerships and disease prevention interventions 19,20 . Most studies raise the need to better understand "the relationship between perceived barriers to accessing services and dissatisfaction with services" 15 in order to promote health equity in our communities.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies identifying barriers to accessing health and social services have reported high rates of self-reported access issues, and have identi ed that those reporting access issues were more likely to be socially and economically vulnerable or suffering from mental health conditions indicating that those who have the hardest time accessing services may be the most in need 16,17 . Studies identifying how barriers to clinical and social services can be reduced use targeted social support interventions and speci c navigation models to promote patient-centered health improvements 18 as well as strategies to evaluate local resources to develop partnerships and disease prevention interventions 19,20 . Most studies raise the need to better understand "the relationship between perceived barriers to accessing services and dissatisfaction with services" 15 in order to promote health equity in our communities.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational partnerships serve to enhance community capacity and intervention sustainability and to foster mutual learning, understanding, and trust. Community coalitions can be especially useful in formalizing partnerships, attending to diverse perspectives, and promoting resource sharing and sustainability [70,88]. As funding policies are beginning to require partnerships (e.g., HIV-testing programs must have linkage partners), a more collaborative approach is imperative.…”
Section: Benefits and Challenges Of Organization-engaged Partnershipsmentioning
confidence: 99%
“…Thus, research should continue to use innovative strategies to develop and sustain direct partnerships with adolescents and consider the role that community-based youth-serving organizations can play in HIV prevention and care. Ongoing community collaborations to address structural level changes are useful in decreasing the incidence of HIV and keeping adolescents with HIV healthy [70,88].…”
Section: Research Needs and Prioritiesmentioning
confidence: 99%
“…Various phases of C2P, including theory, coalition formation, structural and organization functioning, and process measures, have been described in detail elsewhere (Chutuape et al, 2010; Deeds et al, 2008; Geanuracos et al, 2007; Willard et al, 2012; Ziff et al, 2006). Each ATN site’s local institutional review board approved or exempted this research.…”
Section: Introductionmentioning
confidence: 99%
“…C2P was founded on the best practices in the field of community mobilization (Watson-Thompson, Fawcett, & Schultz, 2008) and, to our knowledge, is the only initiative of its kind in focus, scope, and longevity addressing HIV prevention among youth. Various phases of C2P, including theory, coalition formation, structural and organization functioning, and process measures, have been described in detail elsewhere (Chutuape et al, 2010; Deeds et al, 2008; Geanuracos et al, 2007; Willard et al, 2012; Ziff et al, 2006). Each ATN site’s local institutional review board approved or exempted this research.…”
Section: Introductionmentioning
confidence: 99%